Butterfly Species and Nectar Source Preferences at Khairun University Campus, Ternate, North Maluku - WD. Syarni Tala; Ningsi Saibi; Yusmar Yusuf; Magfirah Rasyid; Aswal Salewangeng (UNIVERSITAS KHAIRUN, 2025)
Butterflies have a very important ecological role in the ecosystem, one of which is to help pollinate flowering plants. The existence of butterflies in an area is highly dependent on the availability of nectar sources as the main food for adult butterflies. This study aims to identify the species of butterflies found in the Khairun University campus environment and inventory flowering plants that have the potential to become nectar sources. This research was conducted at campus I of Khairun University, Akehuda, North Ternate Subdistrict, Ternate City, North Maluku during November 2024. Data were collected using the visual encounter survey method by directly observing and recording the species of butterflies that flew and landed on flowers, as well as the species of flowering plants found. Data collection was carried out in the morning at 08:00-10:00 WIT and in the in the afternoon at 16:00-18:00 WIT (Eastern Indonesian Time) according to the time of butterfly activity. Based on the results of the study, it is known that the butterflies found in the campus I, Khairun University consist of 8 species from 3 families, namely the Lycaenidae, Nymphalidae, and Pieridae families. There are 11 species of flowering plants that have the potential as a source of nectar for butterflies in this campus. Tridax procumbens is a flowering plant species that could be a source of nectar for all species of butterflies in the campus environment of Khairun University.